2019
DOI: 10.1371/journal.pone.0216790
|View full text |Cite|
|
Sign up to set email alerts
|

Suitability and safety of L-5-methyltetrahydrofolate as a folate source in infant formula: A randomized-controlled trial

Abstract: L-5-methyltetrahydrofolate is the predominant folate form in human milk but is currently not approved as a folate source for infant and follow-on formula. We aimed to assess the suitability of L-5-methyltetrahydrofolate as a folate source for infants. Growth and tolerance in healthy term infants fed formulae containing equimolar doses of L-5-methyltetrahydrofolate (10.4 μg/ 100 ml, n = 120, intervention group) or folic acid (10.0 μg/ 100 ml, n = 120, control group) was assessed in a randomized, double-blind, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…Long term supplementation of (6S)-5-Methyl-THF-Ca in women (i.e., non-pregnant, or lactating mothers) leads to higher RBC-folate and serum folate compared to the concentrations obtained after folic acid [18,25]. A recent randomized-double blind controlled trial in infants has shown that RBC-folate concentrations were higher at 3 months follow up in the group that received milk fortified with (6S)-5-Methyl-THF-Ca compared to the group that received milk fortified with folic acid, although plasma (6S)-5-Methyl-THF did not differ between the groups [26]. It might be argued that folic acid is readily assimilated by tissues as it is reduced to tetrahydrofolate and trapped in the cells after polyglutamation, whereas (6S)-5-Methyl-THF needs to be converted to tetrahydrofolate before being stored.…”
Section: Discussionmentioning
confidence: 99%
“…Long term supplementation of (6S)-5-Methyl-THF-Ca in women (i.e., non-pregnant, or lactating mothers) leads to higher RBC-folate and serum folate compared to the concentrations obtained after folic acid [18,25]. A recent randomized-double blind controlled trial in infants has shown that RBC-folate concentrations were higher at 3 months follow up in the group that received milk fortified with (6S)-5-Methyl-THF-Ca compared to the group that received milk fortified with folic acid, although plasma (6S)-5-Methyl-THF did not differ between the groups [26]. It might be argued that folic acid is readily assimilated by tissues as it is reduced to tetrahydrofolate and trapped in the cells after polyglutamation, whereas (6S)-5-Methyl-THF needs to be converted to tetrahydrofolate before being stored.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to any ART attempt, dietary supplementation with 5-MTHF (5-methyl tetra hydrofolate: Impryl R , Metafolin R , Tetrafolic R ), the compound that lies immediately downstream from MTHFR, should be recommended for both members of the couple, instead of folic acid. This strategy has yielded good results in patients with a lengthy duration of infertility [17]: it decreases serum homocysteine [24,37], and its safety and efficacy are proven [37][38][39]. Synthetic folic acid has a low capacity for entering the folate cycle [40,41] and is very poorly effective and transformed into 5-MTHF in carriers of MTHFR SNPs [28,29]; Moreover, treatment with folic acid at high doses (5 to 15 mG/day) is known to cause an unmetabolized folic acid (UMFA) accumulation, a source of health questioning [42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency and safety of 5-MTHF has been established, including in children [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], and has been demonstrated to be at least as efficient as FA in reducing homocysteine levels in healthy women [ 38 , 39 ]. It is effective in reducing Hcy in men and women of reproductive age who are carriers of the MTHFR T677T variant [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Folate Malabsorptionmentioning
confidence: 99%